Transparency in Plantation Sector: Access of Cultivation Rights Title Document - Herry M. Polontoh (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
The research aimed to analyze the implementation of the principle of transparency by the National Land Agency to access cultivation rights title documents in the plantation sector. It is empirical legal research. It was conducted at the Office of the National Land Agency of Gorontalo district, Gorontalo province, Indonesia. The results show that the principle of transparency of cultivation right title by the National Land Agency had yet to be implemented as instructed by the judge in the Decision of Supreme Court No. 121 K/TUN/2017. It is caused by the consideration of the National Land Agency that the document of right cultivation title is included in an undisclosed document; hence, if it is public, it violates the company's privacy provisions and applicable regulations. The implementation of the principle of transparency by the National Land Agency to access cultivation right title documents in the plantation sector have yet to be effective because it is influenced by the attitude of professionalism of the National Land Agency, which exercises its duties as applicable regulations.